Inhibitory effects and amino acid metabolism regulations of active polyphenol from foxtail millet bran on chronic colitis in mice - Yang, Ruipeng; He, Shuiling; Wang, Jingli; Yang, Jieya; Su, Ruijun; Zhao, Wenjing (Frontiers in Nutrition, 2025)
IntroductionInflammatory bowel disease (IBD) is frequently associated with metabolic imbalances. Polyphenols have demonstrated efficacy in alleviating colitis by restoring the metabolic disorders. Our previous studies revealed that bound polyphenols extracted from millet bran could alleviate acute colitis and colitis-associated colorectal cancer (CRC) via restoring the gut microbiome and that the low molecular weight (MW) (<200 Da) portion of bound polyphenol (BPLP) constituted the primary active component, comprising six phenolic acids.MethodsTo further evaluate the effects of BPLP on inflammation, a dextran sodium sulfateb(DSS)-induced experimental colitis model was constructed, and BPLP was gavaged on mice. The effects of BPLP on colitis were assessed by detecting the weight, mouse status, gut barrier integrity, and inflammatory cytokine secretion. Additionally, non-targeted metabolomics was used to identify altered metabolites.Results and discussionBPLP administration restored body weight and colon length, protected epithelial structure from DSS-induced damage, and relieved chronic colitis. In colons, BPLP reduced the levels of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β), enhanced the secretion of the anti-inflammatory cytokine IL-10, and upregulated the expression of tight junction proteins. Nontarget metabolomic results showed that BPLP alleviated colitis by modulating amino acid metabolism pathways, including valine/leucine/isoleucine biosynthesis,phenylalanine/tyrosine/tryptophan biosynthesis, and phenylalanine metabolism. Furthermore, alterations in specific amino acids, such as valine and beta-alanine, were consistent with profiles observed in clinical IBD patients. Collectively, these results indicate that BPLP effectively alleviates chronic colitis in mice and regulates inflammation-related amino acid metabolism in vivo.